Prospects for a MERS-CoV spike vaccine - Yusen Zhou; Shibo Jiang; Lanying Du (Taylor & Francis Group, 2018)
Introduction: Six years have passed since Middle East respiratory syndrome (MERS) coronavirus (MERS-CoV), a newly emerging infectious virus, was first reported in 2012. Although MERS-CoV has had a consistently high mortality rate in humans, no vaccines have been approved to prevent MERS-CoV infection in humans. MERS-CoV spike (S) protein is a key target for development of MERS vaccines. Areas covered: In this review, we illustrate the structure and function of S protein as a vaccine target, describe available animal models for evaluating MERS vaccines, and summarize recent progress on MERS-CoV S-based vaccines, focusing on their ability to elicit antibody and/or cellular immune responses, neutralizing antibodies, and protection against MERS-CoV infection in different models. Prospects for future MERS-CoV S-based vaccines are discussed. Expert commentary: The majority of MERS vaccines under development are based on MERS-CoV S protein, including full-length S, S1, and receptor-binding domain (RBD). While it is essential to evaluate the safety of full-length S and S1-based MERS vaccines, further improvement of the efficacy of RBD-based vaccines using novel strategies would be necessary. Overall, this review provides informative guidance for designing and developing safe and effective MERS vaccines based on viral S protein.